Effect of polyethylene glycol (PEG) molecular weight and nanofillers on the properties of banana pseudostem nanocellulose films. (1st February 2019) - Faradilla, RH Fitri; Lee, George; Sivakumar, Pavallam; Stenzel, Martina; Arcot, Jayashree
Highlights: Molecular weight of PEG affected the properties of banana pseudostem nanocellulose films. PEG 1000 improved nanocellulose film flexibility by approximately 100%. Intercalated nanoclay in nanocellulose matrix was detected after PEG addition. Nanofiller significantly increased contact angle of PEG plasticized nanocellulose films. Abstract: The aims of this study were to investigate the effects of polyethylene glycol (PEG) molecular weight (MW) and PEG interaction with nanofillers (nanoclay and graphene oxide) on the properties of banana pseudostem nanocellulose films. PEG MW significantly affected the properties of the films. Low MW PEGs (400 and 1000 g/mol) had better interaction with nanocellulose than the PEG with higher MW and improved the flexibility of the films by about 100%. Interaction between PEG1000 and nanofillers significantly modified the properties of the composite films. PEG1000 had a good interaction with nanoclay, which was reflected by the formation of intercalated nanoclay in the cellulose matrix. The presence of nanoclay and graphene oxide in the PEG plasticised films improved the tensile strength and contact angle of the films compared to the film that only contained PEG. These findings suggest that the properties of banana pseudostem nanocellulose film can be improved by combining PEG with nanofillers.